Sistem Informasi Manajemen di MIN 1 Kota Sawahlunto - Elizasri, Elizasri; Bustamam, Risman (PT PUSTAKA CENDEKIA GROUP, 2023)
The increasing use of information technology, especially the internet, has enabled everyone to carry out various activities more accurately, with quality and quickly. Every organization can take advantage of the internet and information technology networks to carry out various activities electronically. Managers in various organizations are also expected to be able to analyze their performance on a constant and consistent basis with the utilization of available information technology. Utilization of information technology is associated with its importance in the management decision-making process. We can see that there is still a lack of organizations both in the public sector and organizations in the private sector that apply management information systems in decision making, especially in local government organizations. Information systems have a set of information components that are integrated with each other to produce specific goals. The management information system at MIN 1 Sawalunto can run well because it is supported by sophisticated technology, quality human resources and organizational commitment. Management information systems have an important role in the function of operational management and decision making. This system is also a very useful tool for the purpose of reviewing and controlling company operations. The main objective of the system at Min 1 Tanah Datar is to organize all the data collected from every level of the company, summarize it, and present it in a way that facilitates and improves the quality of decisions taken to increase the profitability and productivity of the company. The existence of an information system in a company can really help employees work so that their work becomes effective and efficient. Applications like this are also useful for start-up companies where they produce an effective and efficient information system management model to achieve maximum results for business start-ups.